A study of risk factors in young patients of myocardial infarction - Akram, Mohd Vaseem; Zaidi, Farina; Bansal, Shivani; Kishore, Kaushal (International Journal of Research in Medical Sciences, 2017)
Background: Coronary Artery Disease (CAD) is the major cause of morbidity and mortality burden in the world. Young patients with CAD are specific subset of population requiring attention. A variety of possible contributing factors that include substance abuse, coronary artery anomalies, hypercoagulablestate, oral contraceptive use in young women have been implicated for the pathogenesis of myocardial infarction. The purpose of this study is to collect data of young patients presenting with AMI so that it would be helpful in future for better management in this particular group of patients. Aim of the present investigation was to study clinical profile of acute myocardial infarction in young patients 18-45 years of age and to study the incidence of various risk factors in young patients with myocardial infarction. Methods: The study was conducted in Department of medicine of Santosh medical college & hospital. Study was conducted on 50 cases of acute myocardial infarction if they satisfied the following selection criteria after getting formal consent and ethical clearance. Results: In our study, we have examined patients of myocardial infarction who are aged between 18-45 yrs. and other eligibility criteria for the assessment of modifiable and non-modifiable risk factors in Ghaziabad area. The ratio of male to female sex ratio in our study is 5.25:1 and 64% of the patients in present study had anterior wall MI while 24% had inferior wall MI and 12% had antero-septal wall MI. Conclusions: Mean age of study group is 36.24 ±4.32 years. The maximum number of patients was in 35-40 years of age. Youngest patient was 25 years old male. The incidence of acute myocardial infarction is increasing in younger age group.